How Liberal is Nepal's Liberal Grade Promotion Policy? - Sharma, Dhiraj (World Bank, Washington, DC, 2016)
This paper estimates the magnitude of liberal grade promotion in public schools in Nepal by comparing the pass rate in internally administered exams with the pass rate in the district-exam whose scores determine grade transition. The pass rate in the year-end exam is three and a half times as high as the pass rate in the internal exams. The difference is not explained by an increase in student effort and it is not due to the financial incentives for which students in a random subset of schools were eligible. The paper concludes with a discussion of the policy implications of the findings on the student assessment system in Nepal.